Perancangan Sistem Informasi Pelayanan Administrasi Desa Berbasis Website Pada Desa Situterate Menggunakan Framework Laravel - Armando, Dezan Ade; Mansyuri, Umar; Arief, Rahadian (Universitas Pakuan, 2025)
DESIGN OF A WEBSITE-BASED VILLAGE ADMINISTRATION SERVICE INFORMATION SYSTEM IN SITUTERATE VILLAGE USING THE LARAVEL FRAMEWORKCurrently, the administrative service process at the Situterate Village Office is still carried out manually, including data management related to the administration of these services. This research aims to design a website-based information system for the Situterate Village Office. The system is designed to provide village information, facilitate online mail submission, and simplify administrative management, such as creating cover letters and storing population data. The design of a web-based village service administration information system in Situterate Village was carried out using the Waterfall method. This method involves stages that are carried out sequentially, namely needs analysis, system design, implementation, testing, and maintenance. The results of the study show that services in Situterate Village are still not digital-based and still use a manual system. Therefore, the author took the initiative to design a website-based service information system to improve the efficiency and quality of services to the community. The conclusion of this study shows that a website-based village service information system is very important to make it easier for employees to provide services to the community and make the village administration service process more efficient.